Proposed system for data security in distributed computing in using triple data encryption standard and Rivest Shamir Adlemen - Shawkat S.A.; Tuama B.A.; Al-Barazanchi I. (Institute of Advanced Engineering and Science, 2023)
Cloud computing is considered a distributed computing paradigm in which resources are provided as services. In cloud computing, the applications do not run from a user's personal computer but are run and stored on distributed servers on the Internet. The resources of the cloud infrastructures are shared on cloud computing on the Internet in the open environment. This increases the security problems in security such as data confidentiality, data integrity and data availability, so the solution of such problems are conducted by adopting data encryption is very important for securing users data. In this paper, a comparative study is done between the two security algorithms on a cloud platform called eyeOS. From the comparative study it was found that the Rivest Shamir Adlemen (3kRSA) algorithm outperforms that triple data encryption standard (3DES) algorithm with respect to the complexity, and output bytes. The main drawback of the 3kRSA algorithm is its computation time, while 3DES is faster than that 3kRSA. This is useful for storing large amounts of data used in the cloud computing, the key distribution and authentication of the asymmetric encryption, speed, data integrity and data confidentiality of the symmetric encryption are also important also it enables to execute required computations on this encrypted data. 2022 Institute of Advanced Engineering and Science. All rights reserved.